Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1108/mhrj-01-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy in non-western countries: a review of the recent literature

Abstract: Purpose – The purpose of this paper is to produce a comprehensive and tabulated review of the many and scattered papers on public mental health literacy, with particular focus on people's ability to recognise mental illness and beliefs about the treatment. Design/methodology/approach – This was a review and tabula study. Comprehensive tables describe studies: the first looks at the beliefs of three different groups (the general public, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 99 publications
4
62
1
4
Order By: Relevance
“…The importance of seeking to understand the knowledge and beliefs of refugee populations concerning the nature and treatment and mental problems is increasingly recognised [24]. Research of this kind has implications for the refinement of clinical interventions and the development of tailored health promotion and early intervention programs.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of seeking to understand the knowledge and beliefs of refugee populations concerning the nature and treatment and mental problems is increasingly recognised [24]. Research of this kind has implications for the refinement of clinical interventions and the development of tailored health promotion and early intervention programs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the time elapsed between the course and the receipt of the feedback form and the psychometric properties of the items used to assess MHL confidence are unknown. Finally, because MHFA is limited to a Western model of MHL and because culture influences the ways in which mental illnesses are defined, understood, and treated, conclusions regarding the impact of MHFA on MHL must be interpreted with caution (2). …”
Section: Discussionmentioning
confidence: 99%
“…Studies on the construct of mental health literacy (MHL), as described by Jorm and colleagues (1), indicate that large segments of the public lack knowledge about mental disorders as defined by the DSM and have misconceptions that could affect symptom recognition, management, or prevention (2). Yet MHL appears to be one of the strongest predictors of both help seeking and disclosure of symptoms, and effective strategies for improving MHL are needed (3).…”
mentioning
confidence: 99%
“…MHL studies carried out in Eastern/Asian countries have shown that the recognition of mental disorders and general MHL were generally poorer than in the West/Europe (Furnham & Hamid, 2014). For instance, Altweck, Marshall, Ferenczi and Lefringhausen (2015) found, as predicted, that Indians were less knowledgeable about anxiety disorder, depression and schizophrenia than European Americans and that greater recognition predicted greater endorsement of social causes of mental illness and endorsement of professional help-seeking.…”
Section: Introductionmentioning
confidence: 86%